(untitled) (Swiss Medical Weekly, 2012)
QUESTION UNDER STUDY/PRINCIPLES: Ambulatory care is a mandatory component of post-graduate training in general internal medicine. Academic outpatient clinics face challenges in training residents in terms of exposure to sufficient patient case-mix, diversity of clinical activities and continuity of care while fulfilling their mission to provide care to vulnerable populations. We report the development and evaluation of a new postgraduate curriculum in ambulatory care in Geneva, Switzerland, designed to overcome such challenges. METHODS/DESCRIPTION: The content of learning activities was adapted to core competencies and learning objectives. In the new 2-year curriculum, residents had their working week divided into 2½ days of continuity clinic over two years, and 2½ days of 6 to 12 months rotations (e.g., walk-in clinics). Team work was consolidated through the creation of subunits including an attending physician, 1–2 senior residents during one year and 6- to 8 residents, who met in bi-monthly meetings with other health professionals. RESULTS/EVALUATION: In both local and national surveys, residents and senior residents expressed an overall global satisfaction with the new curriculum. Nursing and administrative staff were less satisfied, because of reduced residents’ time in each unit. Interprofessional meetings were highly appreciated for both patient care and team building. Management of residents’ absences became more complex. CONCLUSION: The new curriculum met its goals in gaining residents’ satisfaction and in reinforcing interprofessional collaboration although management of human resources became more complex. It also gave insights into challenges to be addressed when disseminating a new curriculum, such as strong leadership, educational expertise and management skills and tools.